Inexpensive multigram-scale synthesis of cyclic enamines and 3-N spirocyclopropyl systems. Issue 4 (5th January 2018) - Kumar, Pratik; Zainul, Omar; Laughlin, Scott T.
Abstract : Cyclic enamines are important synthons for many synthetic and pharmacological targets. We report a method for the synthesis of cyclic enamines with exocyclic double bonds and four- to seven-membered rings that permits usage of common N -protecting groups and tolerates functionality round the ring system. Abstract : Cyclic enamines are important synthons for many synthetic and pharmacological targets. Here, we report an inexpensive, catalyst-free, multigram-scale synthesis for cyclic enamines with exocyclic double bonds and four- to seven-membered rings. This strategy is more conducive to scale up, permissive of functionalization around the cyclic system, and less sensitive to the nature of the N -protecting group than previously-described methods for cyclic enamine synthesis. Further, we explore application of these enamines to the synthesis of highly-strained spirocyclic 3N-cyclopropyl scaffolds.